Pengaruh model problem based learning terhadap keterampilan proses sains dasar dan hasil belajar siswa pada konsep sistem pencernaan makanan pada manusia - Deratama, Devi; Surahman, Endang; Fitriani, Rita (Assimilation: Indonesian Journal of Biology Education, 2020)
The purposes of this research were to investigate the effect of problem based learning models on basic science process skills and student learning outcomes on the concept of a food digestive system in humans. The subjects of this study were students of class XI MIPA of SMA Negeri 1 Tasikmalaya City in two classes. The method that was being used in this research was true experiment. The sample was being taken by cluster random sampling method. To measure the basic science prosess skills of the students used an instrument which consists of 12 questions in the form of essay and to measure the learning outcomes used test consists of 30 questions in the form of multiple choice with 5 option. The analysis technique was ANCOVA (analysis of covariance). The results of this research revealed that there was an impact of the problem based learning model to basic science process skills and learning outcomes of learners on the concept of food digestion system in human and there was a relationship between basic science process skills and learning outcomes. Through this research, we found that the higher the basic science process skills of the students, therefore it will impact to the learning outcomes of the students to be better.